1998
DOI: 10.1038/sj.onc.1202108
|View full text |Cite
|
Sign up to set email alerts
|

The germinal center kinase (GCK)-related protein kinases HPK1 and KHS are candidates for highly selective signal transducers of Crk family adapter proteins

Abstract: Adapter proteins function by mediating the rapid and speci®c assembly of multi-protein complexes during the signal transduction which guards proliferation, dierentiation and many functions of higher eukaryotic cells. To understand their functional roles in dierent cells it is important to identify the selectively interacting proteins in these cells. Two novel candidates for signalling partners of Crk family adapter proteins, the hematopoietic progenitor kinase 1 (HPK1) and the kinase homologous to SPS1/STE20 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 37 publications
0
66
0
Order By: Relevance
“…RIPA-lysates were prepared as described (Oehrl et al, 1998). The antibodies used for immuno-complex kinase assay were selected for best speci®city: c-Abl was precipitated from NIH3T3 cell lysates with anti-Abl (Ab-3), Arg with polyclonal anti-Arg serum from Abl 7/7 /cell lysates, Bcr-Abl with anti-Bcr from NIH3T3 Bcr-Abl cell lysates and Tel-Abl from Ba/F3 Tel-Abl cell lysates with anti-Myc.…”
Section: Kinase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…RIPA-lysates were prepared as described (Oehrl et al, 1998). The antibodies used for immuno-complex kinase assay were selected for best speci®city: c-Abl was precipitated from NIH3T3 cell lysates with anti-Abl (Ab-3), Arg with polyclonal anti-Arg serum from Abl 7/7 /cell lysates, Bcr-Abl with anti-Bcr from NIH3T3 Bcr-Abl cell lysates and Tel-Abl from Ba/F3 Tel-Abl cell lysates with anti-Myc.…”
Section: Kinase Assaysmentioning
confidence: 99%
“…For analysis of CRKL/Tel-Abl complexes, Ba/F3 Tel-Abl cells and parental Ba/F3 cells were extracted with 1% Triton X-100 lysis bu er as described previously (Oehrl et al, 1998). After preclearing on protein A-Sepharose and preabsorption on immobilized immunoglobulins from normal rabbit serum, the supernatant was ®nally incubated overnight with immobilized anti-CRKL or an equal amount of immunoglobulins from non-immunized rabbits as indicated.…”
Section: Co-immunoprecipitationsmentioning
confidence: 99%
“…JNK cascade (Hu et al, 1996;Wang et al, 1997;Zhou et al, 1999). HPK1 may mediate extracellular signals through interaction with Src-homology 3 (SH3) domaincontaining adaptor molecules (Ana® et al, 1997;Oehrl et al, 1998;Ling et al, 1999). Here we report that HPK1 was cleaved by caspase activity during apoptosis.…”
Section: Introductionmentioning
confidence: 68%
“…One interesting structural feature of HPK1 is its four proline-rich motifs (putative SH3 domain-binding sites) in its regulatory region (Hu et al, 1996). We and others found that HPK1 physically interacts with adaptor molecules including Crk, CrkL, and Grb2 via these proline-rich motifs (Ana® et al, 1997;Oehrl et al, 1998;Ling et al, 1999). Co-expression of Crk with CrkL enhances HPK1 activity through mechanisms yet unknown (Ling et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation